Growth and survival of pacu Piaractus mesopotamicus (Holmberg, 1887) juveniles reared in ponds or at different initial larviculture periods indoors - Jomori, R. K.; Carneiro, D. J.; Malheiros, E. B.; Portella, M. C. (Elsevier B.V., 2003)
Five-day-old pacu larvae (Piaractus mesopotamicus) with average length and weight of 5.96 mm and 0.42 mg, respectively, were reared as follows: in a semi-intensive system with larvae stocked directly into fertilized ponds (IL0)-and an initial intensive larviculture system with larvae maintained in a laboratory for 3 (IL3), 6 (IL6) and 9 (IL9) days, before being transferred to fertilized ponds. During the indoor phase, larvae were fed Artemia nauplii. Intensive-culture survivals were high (95.6%, 86.4% and 83.8% for IL3, IL6 and IL9, respectively) and at the end of the 45-day period, the longer the larvae were kept in the intensive system, the better the juvenile survival in the ponds. IL9 and IL6 survival rates were 54.0% and 45.4%, respectively, significantly higher (P < 0.05) than IL0 (11%) and IL3 presented an intermediate rate (25.3%). Due to the low survival rate of IL0, length and weight were higher (P < 0.05) when compared to IL6 and IL9; and the differences between their survival rates affected size distribution of juveniles among treatments. Treatments, which resulted in high survival (IL6 and IL9), presented a great number of small fish. In contrast, IL0 and IL3 produced many large and extra large individuals. In general, the results indicate that pacu juvenile production by initial intensive larviculture (IL6 and IL9) was the most efficient method. Therefore, further studies should be conducted in order to improve larval growth in the laboratory and handling techniques in both the laboratory and ponds. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Piaractus mesopotamicus; intensive larviculture; semi-intensive larviculture; Artemia; ponds; juvenile